Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1177/0363546511429278
|View full text |Cite
|
Sign up to set email alerts
|

Former Male Elite Athletes Have a Higher Prevalence of Osteoarthritis and Arthroplasty in the Hip and Knee Than Expected

Abstract: Background: Intense exercise has been reported as one risk factor for hip and knee osteoarthritis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
133
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(148 citation statements)
references
References 30 publications
8
133
0
2
Order By: Relevance
“…The causality behind the low fracture risk found in former male athletes is debated, A recent study has reported BMD z-seores around LO in retired athletes (32), which hypothetically would halve the fracture risk (1,5,22), On the confrary, most prospective confrolled studies which have followed athletes from active career into retirement indicate a higher rate of BMD loss during the frrst decade after retirement than would be expected with age (10,27,34), Whether this high rate is temporary or persists with long-term retirement has not been clarified, although cross-sectional studies in elderly former athletes infer that all benefits in BMD will be lost after decades of retirement (6,15,17), Because exercise is also reported to produce larger bone size (19,21), and if the benefits remained long term (1,6), this would modulate fracture risk as bone size contributes to bone strength and fracture risk independently of BMD (1,2,6,8,35), Residual benefits in neuromuscular ftmetion may influence fracture risk too as it influences the risk of sustaining falls (5,24,29,30), To complicate the issue even frjrther, exercise on a high level has shown to be associated with an increased incidence of soft tissue hip (7) and knee (20,33) injuries and prevalence of hip and knee OA (23,33), conditions that may lead to a less active lifestyle that is accompanied by low BMD (5) and a higher fracture risk (1,5,22), The low level of physical activity may also lead to less exposure to trauma and thereby, hypothetieally, a lower fracture risk (3,15),…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The causality behind the low fracture risk found in former male athletes is debated, A recent study has reported BMD z-seores around LO in retired athletes (32), which hypothetically would halve the fracture risk (1,5,22), On the confrary, most prospective confrolled studies which have followed athletes from active career into retirement indicate a higher rate of BMD loss during the frrst decade after retirement than would be expected with age (10,27,34), Whether this high rate is temporary or persists with long-term retirement has not been clarified, although cross-sectional studies in elderly former athletes infer that all benefits in BMD will be lost after decades of retirement (6,15,17), Because exercise is also reported to produce larger bone size (19,21), and if the benefits remained long term (1,6), this would modulate fracture risk as bone size contributes to bone strength and fracture risk independently of BMD (1,2,6,8,35), Residual benefits in neuromuscular ftmetion may influence fracture risk too as it influences the risk of sustaining falls (5,24,29,30), To complicate the issue even frjrther, exercise on a high level has shown to be associated with an increased incidence of soft tissue hip (7) and knee (20,33) injuries and prevalence of hip and knee OA (23,33), conditions that may lead to a less active lifestyle that is accompanied by low BMD (5) and a higher fracture risk (1,5,22), The low level of physical activity may also lead to less exposure to trauma and thereby, hypothetieally, a lower fracture risk (3,15),…”
Section: Discussionmentioning
confidence: 99%
“…The mailed questionnaire, previously used in similar studies (15,27,33), included the evaluation of lifestyle characteristics such as nutrition, alcohol, smoking, occupational load, weekly hours of prior athletic training and competing, and current leisure-time physical activity. Also, data on anthropometries (weight and height) and fracture incidences were self-reported.…”
Section: Methodsmentioning
confidence: 99%
“…A power calculation was based on the assumption of approximately 14% and 19% prevalence of hip and knee OA,4 and 15% and 25% for hip and knee pain 16 17. With the assumptions of a 30% response rate from GB Olympians aged 40 years and older, assuming all exposures could at least be dichotomised into binary variables and assuming a ratio of exposed to unexposed individuals of 1:1 for any given factor, the study had power of at least 80% to detect ORs of 1.75 and 1.85 or greater for knee pain and knee OA, respectively, at 5% significance.…”
Section: Methodsmentioning
confidence: 99%
“…Sustained focal damage of articular cartilage is the main characteristic of OA, accompanied by muscle weakness, meniscal tears, osteophyte formation, synovial inflammation, and subchondral bone remodelling, which lead to severe joint pains and disability, or even death (6,7). OA is a multifactorial disease and its pathogenesis is complex, mainly involving a strong convergence of environmental susceptibility and genetic risk factors (6,8). OA therapy currently involves approaches to mitigate pain, manage symptoms and slow joint degeneration, and effective treatments to cure the disease have been thus far elusive.…”
mentioning
confidence: 99%